Factory Farms in a Consumer Society - Lavin, Chad (American Studies, 2009)
Originally developed to describe the industrialization of American agriculture, the term “factory farm” became an increasingly pervasive metaphor in American culture through the 20th Century. From its origins in triumphal narratives of agricultural engineering, the term has extended beyond critiques of agribusiness in recent decades and found expression in critiques of the white-collar workplace and allegories of consumerism and colonialism. This paper chronicles this shift, and argues that the expansive use of the metaphor corresponds to our transformation from a producer to a consumer society. This shift to a consumer society is similarly expressed in food writing from the 20th Century, as Upton Sinclair’s focus on the industrial slaughterhouse is replaced with Eric Schlosser’s focus on the fast-food franchise. Wide use of the metaphor of a factory farm reveals not only how disciplinary technologies far exceed the confines of specific industrial settings, but also how seemingly unrelated institutions and activities – like working, eating, and political protest – are organized by the same technologies and discourses.